2015
DOI: 10.1039/c5cc05875a
|View full text |Cite
|
Sign up to set email alerts
|

The construction of a two-dimensional supramolecular organic framework with parallelogram pores and stepwise fluorescence enhancement

Abstract: A novel single-layer two-dimensional (2D) supramolecular organic framework (SOF) with parallelogram pores has been assembled to turn on the fluorescence emission of a non-emissive building block, and the emission could be further enhanced by the aggregation of the as-prepared 2D monolayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 38 publications
4
65
0
Order By: Relevance
“…It has been already reported that TPE-4Q and CB [8] can form a supramolecular organic framework monolayer in 1:2 molecular ratio during the preparation of our manuscript (15). More interestingly, it is found that in our case, a hydrogel could be further formed by the same host and guest components.…”
Section: Formation Of the Supramolecular Hydrogelsupporting
confidence: 49%
See 1 more Smart Citation
“…It has been already reported that TPE-4Q and CB [8] can form a supramolecular organic framework monolayer in 1:2 molecular ratio during the preparation of our manuscript (15). More interestingly, it is found that in our case, a hydrogel could be further formed by the same host and guest components.…”
Section: Formation Of the Supramolecular Hydrogelsupporting
confidence: 49%
“…SEM properties and functions. For instance, Zhao et al (15) reported a highly ordered porous SOF monolayer, by which the fluorescence emission of nonemissive components could be greatly enhanced upon rigid organisation with cucurbituril in water-organic mixed solvent. Supramolecular hydrogels are one of water-based soft materials that have highly variable mechanical properties, which make them increasingly important in biomedical and industrial applications (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 98%
“…The 1 H‐NMR spectrum of PMI1 (0.1 mM) in D 2 O shows three sets of aromatic peaks at 6.5‐8.0 ppm. These peaks gradually disappeared as the CB8 concentration increased and the complete disappearance was affected in the presence of 1 equivalent of CB8, suggesting the possible formation of large self‐assembled structures of CB8• PMI1 complex in D 2 O …”
Section: Resultsmentioning
confidence: 99%
“…However, precise synthesis of highly ordered organic 2D structure is a still challenging task due to synthetic difficulties in forming covalent bonded 2D crystals. Therefore, the reversible supramolecular noncovalent interactions as an alternative or dynamic convent bonding have been utilized to address this concern; despite a few successes, either method tend to afford low stability and lack of fully π conjugation in the synthesized 2D films . Many efforts have been made in exploring new organic reactions and preparation methods to overcome these disadvantages.…”
mentioning
confidence: 99%